A case of sinus arrest caused by opening the mouth under general anesthesia. - Seo, K. (American Dental Society of Anesthesiology, 1994)
We report a case in which transient sinus arrest was observed under general anesthesia. This was associated with opening the mouth and was thought to be caused by a trigeminovagal reflex. The reflex was interrupted by blocking bilaterally the third division of trigeminal nerve.